NariTan: Enhancing Second Language Vocabulary Learning Through Non-Human Avatar Embodiment in Immersive Virtual Reality - Shogo Fukushima; Keigo Sakamoto; Yugo Nakamura (Multimodal Technologies and Interaction, 2024)
With the rise of head-mounted displays (HMDs), immersive virtual reality (IVR) for second-language learning is gaining attention. However, current methods fail to fully exploit IVR’s potential owing to the use of abstract avatars and limited human perspectives in learning experiences. This study investigated IVR’s novel potential by using non-human avatars to understand complex concepts. We developed a system for learning English vocabulary through the actions of non-human avatars, offering a unique learning perspective. This paper presents an IVR vocabulary learning environment with a dragon avatar and compares word retention rates (immediate and one-week memory tests), subjective workload, and emotional changes with traditional methods. We also examined the vocabulary ranges that are teachable using this system by varying the number of avatars. The results showed that the proposed method significantly reduced forgotten English words after one week compared to traditional methods, indicating its effectiveness in the long term.